Practical guide to clinical computing systems : design, operations, and infrastructure - Payne, Thomas H. (Amsterdam : Academic Press, 2015)
Although informatics trainees and practitioners who assume operational computing roles in their organization may have reasonably advanced understanding of theoretical informatics, many are unfamiliar with the practical topics - such as downtime procedures, interface engines, user support, JCAHO compliance, and budgets - which will become the mainstay of their working lives. Practical Guide to Clinical Computing Systems 2nd edition helps prepare these individuals for the electronic age of health care delivery. It is also designed for those who migrate into clinical computing operations roles.
Previous edition: 2008.
Includes bibliographical references and index.
CIP data; item not viewed.
Elsevier
Keywords: Information storage and retrieval systems -- Medical care; Health services administration -- Data processing; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Health services administration -- Data processing; Information storage and retrieval systems -- Medical care; Electronic books; Electronic books